PROFIL KERAJINAN TANGAN ANYAMAN NOKEN DAN AKSESORIS DI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Virgine Alenemey Jufri; Yolanda Holle; Maria Anthoneta Pascahalina Palit (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2020)
The focus of this research is the handicrafts of woven Noken and accessories typical of the people of Papua with the aim to study the raw materials, processes and production produced by Noken craftsmen and accessories. The method used is a qualitative method by understanding and explaining the phenomenon of Noken woven crafts and accessories. The results of the study concluded that (1) The raw materials used in the manufacture of woven bags consist of 3 types, namely ganemo wood fiber (Gnetum gnemon SP), manila yarn, beads, and bia biklen. As for the earring accessories, the main material is Chinese bamboo, (2) The production process of Noken woven is divided into 2 parts, traditional and modern. (4) Products produced in the form of fiber noken, bamboo combs, earrings and bia biklen necklaces